La Disfemia en el aprovechamiento escolar de niños y niñas del cuarto año de educación general básica de la escuela Machala del recinto La Paulina, de la parroquia Puerto Pechiche, cantón Puebloviejo, de provincia de Los Ríos; durante el año lectivo 2011 – 2012 - Cepeda Zapata, Bélgica Danyeline (2012)
He cause that led to our research are the history of the problem and work in research theme as the stammering in the School use of boys and girls from thefourth year of Education Básic School General "Machala" of campus La Paulina, of the Pechiche Port parish, Cantón Puebloviejo, Province of the Rivers; aproblem that was present three years ago in this small group of people referred to above. The problem increases the criteria issued by the family guy who simply responsible of this and other problems to the teacher, situation that with this paper we hope that change or change those negative criteria product of his ignorance. The justification of this research project is the importance of eradicating the problem, by the needs that is passing the child population of the fourth year from the stammering or stuttering. Relevant, is a thorough investigation to find the origin of the cause (stammering), innovative scientific treatments that are, because they are accessible and by their low economic cost, it offers us a possible eradication or solution to the problem. Our work not to be a problem never before investigated underlines its originality and makes it feasible within the educational process. The present research work put an overall objective and three specific for the solution or eradication of the investigated problem ranging in view of providing a good learning and therefore a life of quality. The Variables of this present work are two; the first is the independent as the stammering which is the cause of the problem where originates the problem and the second the subsidiary which is the effect of the subsidiary as it is scholastic achievement. Within the theoretical framework we have scientific theory, in which we support you with scientific theory that gives us the solution or eradication of the problem, by which our work has the following themes and subthemes: •Stammering. •Conduct of the stammering. •Causes of the stammering •Typos of stammering For the purpose of the research is qualitative, and the level is descriptive and explanatory. Field is the place where I make and bibliographic by data collected from books, magazines, etc. The collection of different information was through observation, survey, and the interview that I apply during the investigative process during the current school year. Subsequently the data were tabulated and the results placed on statistical data represented in graphics with the corresponding analysis, to complete this part did with conclusions and recommendations. Using the following methods: the scientist, the method of inductive - deductive, analytical method, historical method - logical. Then make the proposal which arises in a teaching guide with treatments suitable for the enhancement of learning, to thus strengthen quality and safety education in the student